Membangun Karakter Dalam Perayaan Budaya Lokal Di Kabupaten Takalar - Rudi Amir (Prodi PGSD FIP UNM, 2017)
Local culture in a society is an identity and identity for them. The existence of culture in a society, shows that they as a society have a work, taste and copy that they should be proud of. Local culture in its implementation has the value and ability to build the character of the nation for its people, as the celebration of maudu lompoa and appaddekko has a driving force in building the character of the community that celebrates it. There are several characters built in the cultural celebration that can be observed, among others, mutual cooperation, a sense of unity, respect for difference and equality, hard work and brotherhood. Therefore, the local culture should be preserved and given wide space to develop, because it can be a medium of character education transformation for the younger generation.